The Impact of a Flipped Classroom on the Creativity of Students in a Cake Decorating Art Club - Tien, Li-Chu; Lin, Shih-Yen; Yin, Hsiang; Chang, Jen-Chia (Frontiers in Psychology, 2020)
This study was designed to explore the impact of different learning strategies used by the student organizations on cake art creativity. Conducting the questionnaire, classroom observation and in-depth interviews, quasi-experimental design was adopted and 90 hours of experimental teaching was conducted over 16 weeks. The subject is 27 students of Decorated Cake Art Clubs from one of central universities in Taiwan. The results support that in terms of creativity, the community taking flipped classroom learning is significantly better than the community of using traditional learning strategies; furthermore, flipped classroom learning can promote learners’ motivation and satisfaction